Demófilo de Buen Lozano: Freemasonry and exile - Martínez Chávez, Eva Elizabeth (2021)
This article reveals the relation that existed between Demófilo de Buen Lozano and freemasonry.  It explores biographical information and analyzes de Buen Lozano’s participation in the Second Spanish Republic (1931-1939), the Spanish Civil War (1936-1939), and the reprisals he suffered at the hands Francisco Franco, the judicial process to which he was subjected by the Special Tribunal for the Repression of Freemasonry and Communism, and his definite exile in America. The study is based on bibliographic sources but, above all, on documents found in historical archives in Spain and Mexico.